High density lipoprotein and its apolipoprotein-defined subspecies and risk of dementia - Koch, Manja (J Lipid Res, 2020)
Whether HDL is associated with dementia risk is unclear. In addition to apoA1, other apolipoproteins are found in HDL, creating subspecies of HDL that may have distinct metabolic properties. We measured apoA1, apoC3, and apoJ levels in plasma and apoA1 levels in HDL that contains or lacks apoE, apoJ, or apoC3 using a modified sandwich ELISA in a case-cohort study nested within the Ginkgo Evaluation of Memory Study. We included 995 randomly selected participants and 521 participants who developed dementia during a mean of 5.1 years of follow-up. The level of total apoA1 was not significantly related to dementia risk, regardless of the coexistence of apoC3, apoJ, or apoE. Higher levels of total plasma apoC3 were associated with better cognitive function at baseline (difference in Modified Mini-Mental State Examination scores tertile 3 vs. tertile 1: 0.60; 95% CI: 0.23, 0.98) and a lower dementia risk (adjusted hazard ratio tertile 3 vs. tertile 1: 0.73; 95% CI: 0.55, 0.96). Plasma concentrations of apoA1 in HDL and its apolipoprotein-defined subspecies were not associated with cognitive function at baseline or with the risk of dementia during follow-up. Similar studies in other populations are required to better understand the association between apoC3 and Alzheimer’s disease pathology.